Occurrence of Vernonia anamallica (Asteraceae) in Agasthyamalai Biosphere Reserve, southern Western Ghats, India - Jagadeesan, R.; Gangaprasad, A.; Mathew, S. P. (Rheedea, 2016)
Vernonia anamallica Bedd. ex Gamble was described based on the collection from the Anamalai hills, southern Western Ghats. This species was remained unknown until it was rediscovered after 92 years from the Rajamala hills and subsequently known by two more collections from Pettimudi and Konalar. A detailed description along with photographs is provided here for the first time based on our recent collection from the Agasthyamalai Biosphere Reserve (ABR), which also forms an extended distribution of this species.